24
$\begingroup$

I want to prove:

For an integrable function $f(x)$ and periodic with period $T$, for every $a \in \mathbb{R}$, $$\int_{0}^{T}f(x)\;dx=\int_{a}^{a+T}f(x)\;dx.$$

I tried to change the values and define $y=a+x$ so that $dy=dx$ and the limits of the integrals are as we want, but I'm not sure how to use the fact that $f(x)$ is periodic.

Thanks a lot!

$\endgroup$
2
  • 2
    $\begingroup$ Dear Jozef: The simplest, I think, is to do the computation by using a primitive (or anti-derivative) $F$ of $f$. (At the end you can make $F$ disappear.) Also, compute "LHS minus RHS". $\endgroup$ Dec 26 '11 at 15:36
  • 1
    $\begingroup$ Let $N$ be such integer that $N\cdot T \in \langle a,a+T \rangle$. Does dividing the integral as $\int_a^{a+T}=\int_a^{NT}+\int_{NT}^{a+T}$ help? $\endgroup$ Dec 26 '11 at 15:37
23
$\begingroup$

If $F$ is a primitive of $f$, then

$$\int_{a}^{a+T}f(x)\ dx-\int_{0}^{T}f(x)\ dx$$ $$=F(a+T)-F(a)-F(T)+F(0)$$ $$=\Big(F(a+T)-F(T)\Big)-\Big(F(a)-F(0)\Big)$$ $$=\int_T^{a+T}f(x)\ dx-\int_0^af(x)\ dx$$ $$=0.$$

One checks the last equality by making the obvious change of variable, and by using the periodicity.

EDIT 1. What I wrote above is how I remember the computation. Of course, it can be written like that: $$ \int_{a}^{a+T}f(x)\ dx-\int_{0}^{T}f(x)\ dx=\int_T^{a+T}f(x)\ dx-\int_0^af(x)\ dx=0. $$

EDIT 2. Formal justification of the first equality in the above display: $$ \int_0^af(x)\ dx+\int_{a}^{a+T}f(x)\ dx=\int_{0}^{T}f(x)\ dx+\int_T^{a+T}f(x)\ dx. $$

(This formula should appear somewhere...)

$\endgroup$
2
  • $\begingroup$ Dear @Jozef: You're most welcome! $\endgroup$ Dec 26 '11 at 16:34
  • $\begingroup$ Thank you @Pierre-YvesGaillard $\endgroup$
    – A s
    Apr 1 '17 at 11:55
24
$\begingroup$

$$ \begin{align} \int_a^{a+T}f(x)\,\mathrm{d}x-\int_0^{T}f(x)\,\mathrm{d}x &=\left(\color{red}{\int_a^{T}f(x)\,\mathrm{d}x}+\int_T^{a+T}f(x)\,\mathrm{d}x\right)\\ &-\left(\int_0^{a}f(x)\,\mathrm{d}x+\color{red}{\int_a^{T}f(x)\,\mathrm{d}x}\right)\\ &=\int_T^{a+T}f(x)\,\mathrm{d}x-\int_0^{a}f(x)\,\mathrm{d}x\\ &=\int_0^{a}f(x+T)\,\mathrm{d}x-\int_0^{a}f(x)\,\mathrm{d}x\\ &=\int_0^{a}(f(x+T)-f(x))\,\mathrm{d}x\\ &=\int_0^{a}0\,\mathrm{d}x\\ &=0 \end{align} $$

$\endgroup$
3
  • $\begingroup$ Very nice!! But why $\int_0^{a}0\,\mathrm{d}x=0$ ? It should be a constant (call it $k$) $\endgroup$
    – Dor
    Jan 26 '15 at 9:00
  • $\begingroup$ @Dor: The limits make that a definite integral. You are thinking of an indefinite integral or anti-derivative. $\endgroup$
    – robjohn
    Jan 26 '15 at 12:06
  • $\begingroup$ @Dor $\int_0^a0dx=[k]_0^a=k-k=0$ $\endgroup$
    – user50618
    Nov 4 '19 at 11:21
11
$\begingroup$

Here's a picture illustrating the basic idea. (Compare the areas marked with the same color.)

periodic function

$NT$ denotes the integer multiple of $T$ which belongs to the interval $\langle a,a+T \rangle$. (In this example $N=2$.)


In case someone wants to see metapost source for the picture, it is figure 5 from here.

$\endgroup$
10
$\begingroup$

$\int_a^{a+T}f(t)dt=\int_a^Tf(t)dt+\int_T^{a+T}f(t)dt,$ and in the last integral, making the substitution $x=t-T$, we get for $a\in [0,T)$, since $f$ is $T$-periodic $$\int_a^{a+T}f(t)dt=\int_a^Tf(t)dt+\int_0^{a}f(x+T)dx=\int_a^Tf(t)dt+\int_0^{a}f(x)dx=\int_0^T f(t)dt.$$ For $a\in\mathbb R$, take $n\in\mathbb Z$ such that $a+nT\in [0,T)$. Then $$\int_a^{a+T}f(t)dt=\int_{a+nT}^{a+(n+1)T}f(x-nT)dx=\int_{a+nT}^{a+(n+1)T}f(x)dx=\int_0^Tf(t)dt$$ using the previous case.

$\endgroup$
3
  • 2
    $\begingroup$ If I did not miss something, this works for $a\in \langle 0,T \rangle$, but general idea is basically the same. $\endgroup$ Dec 26 '11 at 16:05
  • 1
    $\begingroup$ @MartinSleziak Yes, I have added the details. Thanks. $\endgroup$ Dec 26 '11 at 16:11
  • 1
    $\begingroup$ Thanks a lot! very helpful! $\endgroup$
    – Jozef
    Dec 26 '11 at 16:16
2
$\begingroup$

Here is a simple way using the periodicity of the function and the antiderivative: $$F(x+n\cdot T) = F(x); \ n\in \mathbb{Z}$$ $$ \int^{a+T}_a f(x)dx = F(a+T)-F(a)= F(a) - F(a) = 0 = F(T)-F(0)=\int^T_0 f(x)dx $$

The periodicity carries over from the function to the antiderivative, which is easily seen if you take a look at the fourier series of the periodic function.

$\endgroup$
2
$\begingroup$

$$\begin{align} \int_{a}^{a+T}f(x)\ dx&= \int_{T}^{a+T}f(x)\ dx +\int_{a}^{T}f(x)\ dx\\&\overset{y=x-T}{=} \color{red}{\int_{0}^{a}f(y+T)\ dx} +\int_{a}^{T}f(x)\ dx\\&\overset{periodic}{=} \color{red}{\int_{0}^{a}f(y)\ dx} +\int_{a}^{T}f(x)\ dx\\&=\int_0^Tf(x)\ dx. \end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.